Biosensing: Enhancing the Angular Sensitivity of Plasmonic Sensors Using Hyperbolic Metamaterials (Advanced Optical Materials 11/2016). Issue 11 (16th November 2016) - Sreekanth, Kandammathe Valiyaveedu; Alapan, Yunus; ElKabbash, Mohamed; Wen, Amy M.; Ilker, Efe; Hinczewski, Michael; Gurkan, Umut A.; Steinmetz, Nicole F.; Strangi, Giuseppe
Abstract : K. V. Sreekanth, G. Strangi, and co‐workers demonstrate a grating‐coupled hyperbolic material‐based plasmonic platform that provides extremely high angular sensitivity by exciting the bulk plasmon polaritons associated with hyperbolic metamaterials, on page 1767. This angular‐scan plasmonic biosensor is used for the detection of low molecular weight biomolecules such as biotin and high molecular weight macromolecules such as Cowpea mosaic virus at ultralow concentrations.